2, 2′, 4, 4′-tetrabromodiphenyl ether (BDE-47) induces mitochondrial dysfunction and related liver injury via eliciting miR-34a-5p-mediated mitophagy impairment. (March 2020) - Chen, Feng; Feng, Li; Zheng, Yuan-lin; Lu, Jun; Fan, Shao-hua; Shan, Qu; Zheng, Gui-hong; Wang, Yong-Jian; Wu, Dong-mei; Li, Meng-qiu; Wang, Qing-qing; Zhang, Zi-feng
Abstract: 2, 2′, 4, 4′-Tetrabromodiphenyl ether (BDE-47) is associated with various adverse human health effects; however, the knowledge of its toxicity is still very limited. Mitochondrial injury has been observed in liver cells exposed to BDE-47 in vitro. Mitophagy impairment causes the accumulation of dysfunctional mitochondria, contributing to the pathological mechanisms of liver injury. The aim of this study was to investigate whether BDE-47 impairs mitophagy to trigger mitochondrial dysfunction-related liver injury and the underlying mechanisms. This study revealed that BDE-47 elicited mitochondrial dysfunction and related oxidative liver injury by impairing mitophagy. Moreover, our results showed that NAD + insufficiency is responsible for BDE-47-mediated mitophagy defect and mitochondrial dysfunction in mouse livers, which was associated with suppression of Sirt3/FoxO3a/PINK1 signaling. Furthermore, our results indicated a potential role of miR-34a-5p in the hepatotoxicity of BDE-47. Mechanistically, BDE-47 dramatically upregulated miR-34a-5p expression in mouse livers. The data from AAV-sponge-mediated miR-34a-5p inhibition suggested that miR-34a-5p diminished NAD + level by directly targeting NAMPT expression in BDE-47-treated mouse livers, which was confirmed by luciferase reporter assay. Consequently, miR-34a-5p markedly abated Sirt3/FoxO3a/PINK1 signaling-mediated mitophagy to promote mitochondrial dysfunction in BDE-47-treated mouse livers. The present study provided in vivo evidence to reveal a potential mechanism for BDE-47-induced mitochondrial dysfunction and related liver injury and indicated that miR-34a-5p-mediated mitophagy impairment might be a therapeutic target for BDE-47 toxicity. Graphical abstract: Image 1 Highlights: BDE-47 impairs mitophagy to elicit mitochondrial dysfunction-related hepatotoxicity. Impaired NAD + /Sirt3/parkin signaling contributes to BDE-47-mediated mitophagy defect. Elevated miR-34a-5p by BDE-47 causes NAD + insufficiency by targeting NAMPT expression. MiR-34a-5p promotes BDE-47-induced mitophagy defect by abating Sirt3/parkin signaling. MiR-34a-5p-induced mitophagy defect may be an intervention target for BDE-47 toxicity. Abstract : BDE-47 impairs mitophagy to elicit mitochondrial dysfunction-related liver injury by promoting miR-34a-5p-mediated inhibition of NAD + /Sirt3/parkin signaling.